E-048 Carotid blowout syndrome: emergent endovascular management by stenting. (16th November 2010) - Tisnado, J; Champlain, M Des; Sydnor, M; Komorowski, D; Ehlenberger, C; Fox, W
Abstract : Introduction: Carotid blowout syndrome (CBOS) is a catastrophic emergency associated with high morbidity and mortality. The usual causes are postoperative, inflammation, traumatic, and head and neck tumor invasion. The conventional surgical management is fraught with high morbidity, mortality and complication rates and is ineffective in some cases. This includes carotid artery and/or branch ligation. Carotid artery bypass can be performed with limited success. With the advent of uncovered and covered stents, the emergent management of CBOS has improved and, perhaps, at this time, a desperately fatal disease can be managed with temporary success. Materials and methods: During the past 3  years, we have studied five patients (men and women of middle and advanced age) with CBOS of different etiologies, who were considered difficult or not manageable by emergency surgery. Insertion of different types of both uncovered and covered stents, both self-expanding and balloon expandable was performed: Gore Viabahn Endoprosthesis, iCast (Atrium) covered stent, Fluency Plus Stent-Graft (Bard), Wallstent (Boston Scientific) and Protégé (Bard). Results: The procedures were done in the interventional radiology suite and were successful in temporarily managing the CBOS. No major complications related to the procedures were encountered. No arterial rupture, occlusion, thrombosis, stroke or infection resulted in a short follow-up. Conclusions: Emergent insertion of covered and uncovered stents, self-expanding and balloon expandable, is a safe, effective and easy way to temporarily manage CBOS. A longer follow-up and more patients are necessary to assess the long term role of stenting in CBOS.